Khlōng chīwaprawat, Phra Khrū Wisutthiwongsāčhānyānamunī (Lūangphō̜ Chǣm Wat Chalō̜ng), Wāt Chaiyathārārām, Čhangwat Phūket - Khanit Niyakit (Krung Thēp : Bō̜risat Wœ̄nʻō̜pset Phrinting Čhamkat, 2011)
Biography of Luangpho Chaem, Thai senior monk of Chalong temple or Chaiyathararam temple in Phuket.
Poems.
In Thai.
Keywords: Wisutthiwongsāčhānyānamunī, -- Phra Khrū, -- 1827-1908 -- Teachings; Buddhist monks -- Thailand -- Phuket -- Biography; Religious life -- Buddhism